Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ecog.04307
|View full text |Cite
|
Sign up to set email alerts
|

Climate effects on fish body size–trophic position relationship depend on ecosystem type

Abstract: The energetic demand of consumers increases with body size and temperature. This implies that energetic constraints may limit the trophic position of larger consumers, which is expected to be lower in tropical than in temperate regions to compensate for energy limitation. Using a global dataset of 3635 marine and freshwater ray‐finned fish species, we addressed if and how climate affects the fish body size–trophic position relationship in both freshwater and marine ecosystems, while controlling for the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Interestingly, a study conducted in a Neotropical floodplain river found that the MTL of carnivorous fishes did not increase with mean body size (Layman et al 2005). A possible explanation is that low availability of prey fish at higher trophic positions during certain periods of the annual hydrologic cycle forces large piscivores to feed at lower trophic levels to meet metabolic demands (Arim et al 2007), especially at tropical regions where the temperatures tend to be high (Dantas et al 2019). Research that explores the relationship between MTL and mean body size across multiple species of non‐carnivorous fishes appears to be lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study conducted in a Neotropical floodplain river found that the MTL of carnivorous fishes did not increase with mean body size (Layman et al 2005). A possible explanation is that low availability of prey fish at higher trophic positions during certain periods of the annual hydrologic cycle forces large piscivores to feed at lower trophic levels to meet metabolic demands (Arim et al 2007), especially at tropical regions where the temperatures tend to be high (Dantas et al 2019). Research that explores the relationship between MTL and mean body size across multiple species of non‐carnivorous fishes appears to be lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Large Generalist Predators (LGP) can modify prey-predator interactions, because their bigger body size confer them the ability to feed on a wide variety of prey of different sizes (Woodson et al, 2018). We speculate that behavior responses of P. squamosissimus feeding lower on food chains in both areas evolved because, in higher temperatures, animals have higher relative demand for carbon and digestion of plant tissue is easier, inducing higher rates of herbivory and omnivory (Woodson et al, 2018;Dantas et al, 2019). Generalist and opportunistic species as P. squamosissimus are fundamental to restructure impacted food webs, since they could change interactions and trigger trophic cascades on the new environmental conditions (Bartley et al, 2019) despite to remain in the original trophic position.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature can influence marine ecosystem function at both the system and individual levels. Increasing temperature can cause the metabolism in individuals to increase (Dantas et al, 2019), alter the population structure and phenology of phytoplankton communities (Moisan et al, 2002;Conversi et al, 2010), and result in changes in trait variation within populations (Salo et al, 2020). Consequently, marine ecosystems are reorganizing as temperature influences both range size and species richness (Batt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%